Operations of fuzzy mathematic as a part of information technologies on the Windows platform - Мінаєв, Ю. М.; Філімонова, О. Ю. (Proceedings of National Aviation University, 1998)
Proposed is universal methodics and algorithm of performing operation of fuzzy mathematics with fuzzy numbers and fuzzy variables. The obtained results are adequate to the presupposed primary data. This allows to use the proposed methodics for realization of iteration procedures. Shown is direct dependence of the possibility to receive constructive solution on arithmetic operation structure. Examples are given to illustrate the use of proposed methodology for solution of real applied problems in the Exel medium on Windows platform under conditions of indeterminancy and incomplete information